Pan-stage real-time PCR for quantitation of Trypanosoma cruzi parasitic loads in blood samples. (September 2022) - Ramírez, Juan David; Cao, Liyong; Cruz-Saavedra, Lissa; Hernandez, Carolina; Castañeda, Sergio; Muñoz, Marina; Ballesteros, Nathalia; Banu, Radhika; Shrestha, Paras; Cordon-Cardo, Carlos; Sordillo, Emilia Mia; Paniz-Mondolfi, Alberto
Highlights: The Trypanosoma cruzi parasitic load is not life-stage dependent. Epimastigotes can be used to quantify T. cruzi parasitic loads. Molecular diagnostics of T. cruzi must be improved. Abstract: Chagas disease is a complex zoonosis caused by Trypanosoma cruzi . The diagnosis of this infection is complex and molecular tools are suggested to detect the parasite in blood samples. A long-standing question arises in Chagas disease molecular diagnostics and is related to the feasibility of using epimastigotes in standard curves to quantify parasitic loads. Herein, we conducted experiments running standard curves with all the known life stages of T. cruzi . Our results indicate that regardless of the life stage employed, there are no statistically significant differences when calculating parasitic loads in blood samples. Our results have practical implications from a laboratory perspective in terms of the usability of epimastigotes to build standard curves for T. cruzi pan-stage assessment. Future studies are needed to further improve T. cruzi molecular diagnostic methods and enhance their impact in clinical practice.